AN ANALYSIS OF EFL JUNIOR HIGH SCHOOL STUDENTS’ DIFFICULTIES IN SPEECH PRODUCTION - Yogi Saputra Mahmud (Premise: Journal of English Education and Applied Linguistics, 2018)
This study aims to discover the students’ difficulties in retelling their experiences. Nine Junior High School students participated in this study. Two research instruments were utilized to collect the research data, including spoken text analysis and students’ interview. By analyzing the linguistic features and generic structures of the students’ spoken texts, it is discovered that all students had constructed their stories based on the required elements of recounts. However, most of the students did not elaborate their personal comments on the texts they have spoken. In relation to the grammatical errors, misformation becomes the most general errors found in the students’ spoken texts, followed by omission, addition, and misordering.  The students are also interviewed to reveal their perceptions regarding their speaking difficulties. Based on the interview, limited understanding of verbal forms, vocabularies, as well as anxiety or nervousness are identified as the possible causes of the students’ difficulties. This study also provides further suggestions and implications for classroom teachers as well as recommended directions for future researchers in the relevant field. .